Rule Changes to Increase Shared Medal Winning at the Olympics - Li, Feifei; Hopkins, Will G. (Frontiers in Sports and Active Living, 2022)
One of the most inspirational moments of the Tokyo Olympics was the sharing of the gold medal in the men's high jump. Rule changes that allow more medal sharing when athletes and teams are effectively equal in ability would improve the entertainment value of the Olympics, reward more athletes for their years of dedication to sport, and augment the Olympic ideal of fair play. Medals in most events are decided by a time, distance or points score in a final. When scores differ by 0.1 or less of the variability in the score between competitions, the athlete or team with the better score would obtain a better score on average in only 52% of subsequent competitions, representing medals determined effectively by a coin toss. We have therefore quantified the medal sharing at the Tokyo Olympics that would have occurred if medals had been shared with such score differences in events with known variability between competitions ( 1% for track running, swimming, rowing; 1-2% for kayaking and canoeing; 1-4% for field events). In these events, 10%, 14% and 14% respectively of gold, silver and bronze medals would have been shared. Most of the sharing (68%) would have occurred with male athletes. The variability of performance scores in other events between competitions would need researching to establish maximum score differences for medal sharing in these events. The acceptability of these rule changes to athletes, coaches and spectators would also need to be investigated.